Sutureless Intrascleral Fixation of Secondary Intraocular Lens Using 27-Gauge Vitrectomy System - Todorich, Bozho (Ophthalmic Surg Lasers Imaging Retina, 2016)
Transconjunctival sutureless intrascleral fixation is an important surgical option for secondary intraocular lens (IOL) implantation. In this report, the authors describe the technique of using a 27-gauge platform to perform pars plana vitrectomy, lensectomy, and sutureless scleral IOL fixation in a patient with crystalline lens dislocation secondary to Marfan’s syndrome. Case report and detailed description of the surgical technique are discussed.